A Systematic Review of the Selected Evidences on the Effectiveness of Inter-professional Education (IPE) in Developing Interprofessional Learning Environment - Al Harthy, Said Nasser; Al Subhi, Najla; Tuppal, Cyruz; ReÃ±osa, Mark Donald (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Purpose: This systematic review aimed to provide available evidence in determining for the effectiveness of IPE as a modality in developing interprofessional learning environment for healthcare students.Methods: The computerized searches from 2009-2015 in ten electronic databases were performed. Two independent reviewers were consulted to assess the eligibility, level of evidences and methodological quality in each study. Result: nine out of ten studies were retrieved. These studies include (a) two RCT studies; scored eight and seven out of eight, (b) Three quasi-experimental pretestposttest design; scored seven, six, and six out of eight, (c) Three controlled before and after study; scored six, six, five and five out of eight, and (d) one controlled longitudinal; scored six out of eight respectively.Conclusion: Based on the systematic review, evidence showed that IPE was effective in building strong interprofessional learning environment. On the other hand, the authors recommend considering conduct of similar systematic review grounded on IPE with larger sample size within the health allied discipline.